Servant and steward of the mystery: Colossians 1:26–27; 2:2; 4:3. (November 2019) - May, David M.
Paul's role as servant-steward of the mystery of God was to reveal the object of that mystery, which was Christ. God's mystery was that Christ's life, death, and resurrection reshaped and transformed a person's understanding of history and the future. The mystery also meant the inclusion of gentiles into the community of faith, the suffering of Paul when the proclamation of the mystery was made known, and the presence of Christ in believers, even now.